PENERAPAN PENDIDIKAN KARAKTER TOLERANSI BAGI SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Dariyani, Sritin; Iswandi, Irvan; Humaeroh, Iis (Sindoro: Cendikia Pendidikan, 2024)
This study aims to identify and analyze the implementation of character education focused on tolerance for fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. The method used is descriptive qualitative, employing observation, interviews, and documentation techniques. The results of the research show that the implementation of tolerance character education is carried out through learning activities, interactions between students, and extracurricular programs that support tolerance values. These findings emphasize the importance of an inclusive and collaborative school environment in shaping students' character. It is hoped that the results of this study can serve as a reference for other educational institutions in implementing character education aligned with tolerance values in daily life. From the research conducted, it can be understood that tolerance character is not only taught theoretically in schools but is also truly practiced in daily life, both at school, in dormitories, and in public places. Keywords: character education, tolerance, madrasah;